2014
DOI: 10.1016/j.apmr.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography: The New Frontier in Direct Measurement of Muscle Stiffness

Abstract: The use of brightness-mode ultrasound and Doppler ultrasound in physical medicine and rehabilitation has increased dramatically. The continuing evolution of ultrasound technology has also produced ultrasound elastography, a cutting-edge technology that can directly measure the mechanical properties of tissue, including muscle stiffness. Its real-time and direct measurements of muscle stiffness can aid the diagnosis and rehabilitation of acute musculoskeletal injuries and chronic myofascial pain. It can also he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
200
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(220 citation statements)
references
References 62 publications
1
200
0
3
Order By: Relevance
“…Different ultrasound elastography techniques for evaluating the muscle stiffness have been described, including strain elastography, acoustic radiation force impulse (ARFI) imaging and SWE [22]. Only a small number of studies based on the elastographic assessment of muscle stiffness and indicating the potential application of the method are present in the literature [30,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ultrasound elastography techniques for evaluating the muscle stiffness have been described, including strain elastography, acoustic radiation force impulse (ARFI) imaging and SWE [22]. Only a small number of studies based on the elastographic assessment of muscle stiffness and indicating the potential application of the method are present in the literature [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, only a limited number of studies in the literature have reported the validity of using US elastography in clinical practice for patients with musculoskeletal issues. In these studies, the shear wave elastography (SWE) technique was mostly used to evaluate the normal-physiological parameters of the muscle and tendon components [20][21][22][23][24]. Although these works provided innovative ideas for future studies, they were mostly experimental in design and no practical implementation of US elastography use in the clinical examination of voluntary muscle contraction has been suggested to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SWE which provides quantitative information regarding tissue stiffness has become popular and also is more operator-independent. SWE has gained increasing attention for the evaluation of muscle stiffness [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 The hypothesis of this study was that kinesiology tape would help improve runner performance in a fatigued state by acting like a rubber band when placed on the anterior aspect of the lower limbs to help pull them forwards and aid skeletal muscle's elastic property. [20][21][22][23] Preliminarily, data from this study suggest that kinesiology tape is marginally protective of decreases in step length and stride length among fatigued runners. This study did not test the claim that Rocktape enhances performance in a fatigued state through modification of blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle possesses the property of extensibility (ability to stretch) and elasticity (the ability to recoil). [20][21][22][23] The ability of muscle to stretch and recoil is important to generate force. In a fatigued state, these attributes may be impaired; and deficiencies in running kinematics can occur because of muscle exhaustion.…”
Section: Discussionmentioning
confidence: 99%